PERISTILAHAN AKTIVITAS MENGASUH BAYI DALAM MASYARAKAT MELAYU SAMBAS - Syarifah Istiqomah; Amriani Amir; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe research is focused on activities babysitting in the Sambas Malay community. Activities babysitting are often carried out by the community Sambas in women who already have children. The problem in this study was the nature term, meaning learning the terminology and the implications of the text in babysitting activity in Sambas Malay community.The method used was descriptive with a form of qualitative research. The data source was the informant and the data was in the form of a terminology regarding the activities babysitting in the Sambas Malay community. The technique used was an interview while the data collection tool was in the form of a recording device and a camera from a cell phone, pens and notebooks. Based on the results of the analysis found that 53 data terminology of activities babysitting that which is divided into 5 claisifications parts of activities babysitting, are the term activity, tool term, process term, perpretator term, and traditional term.  Keywords: Activites Babysitting, Malay Sambas Language, Meaning Terminology